THE EXAMINATON OF Salmonella sp. AND Escherichia coli CONTENT ON FISH-PASTE IN KLAMPIS MARKET OF BANGKALAN MADURA AS BIOLOGY LEARNING RESOURCE - Wahdiniati, L; Pantiwati, Yuni; Latifa, Roimil (University of Muhammadiyah Malang, 2016)
Recently, the necessity of foods has been fulfilled by using various methods without considering hygiene level and sanitation during its processing. One of food processing which is assumed as unhygienic cuisine is fish-paste. Fish-paste is commonly made from side product of boiling fish or shrimp. It has a thick viscosity with salty-sweet or sweet-spicy taste and can be used as food seasoning. The study is descriptive qualitative and aimed identify the content of Salmonella sp. and Escherichia coli in fish-paste in Klampis market of Bangkalan Madura; moreover, to assess if the paste is safe to consume and fulfilling the requirement of food-safety-standard based on SNI. The results research were used to compose biology learning resource as practical guidance. This research employed spread-plate method. As many as 7 samples were assessed by three multiplications. The results were compared to Indonesia National Standard 2009 of maximum level of microbe contamination on fish and fish-product including Mollusca, Crustaceae, Echinodermata which were processed. The research results showed that there were no finding neither Salmonella sp nor Escherichia coli on the paste tested. These results were utilized as biology learning resource.